(untitled) (Advancements in Homeopathic Research, 2023)
Sickle cell disease (SCD) is a hereditary blood syndrome that affects the shape and passage of red blood cells (RBCs) in blood vessels, which leads to several medical complications. Normal red blood cells are round or oval. In people with sickle cell disease, the haemoglobin which is a substance present in red blood cells becomes defective and in turn leads to the change in shape of the red blood cells. Red blood cell becomes like sickles or crescent moons in the persons suffering from sickle cell disease. These inflexible, sticky cells may get trapped in small blood vessels, which in turns reduces or blocks blood flow and oxygen to different parts of the body. As such there is no cure for sickle cell disease but homeopathic Medicines can relieve pain and help prevent complications associated with the Sickle cell disease (SCD). In this paper we have presented our research on symptomatic relief in sickle cell disease patients by homeopathy.